2014
DOI: 10.1152/ajpcell.00366.2013
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Wnt/β-catenin signaling promotes epithelial differentiation of mesenchymal stem cells and repairs bleomycin-induced lung injury

Abstract: . Inhibition of Wnt/␤-catenin signaling promotes epithelial differentiation of mesenchymal stem cells and repairs bleomycininduced lung injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 41 publications
2
68
0
Order By: Relevance
“…XAV939 has previously been demonstrated to effectively suppress bleomycin-induced PF in vivo by inhibiting Wnt/β-catenin signaling (Wang et al, 2014). We reproduced this model in the current study and demonstrated again that XAV939 significantly reduced the severity of PF as assessed by H&E (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…XAV939 has previously been demonstrated to effectively suppress bleomycin-induced PF in vivo by inhibiting Wnt/β-catenin signaling (Wang et al, 2014). We reproduced this model in the current study and demonstrated again that XAV939 significantly reduced the severity of PF as assessed by H&E (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mice were sacrificed 7 or 14 days after bleomycin instillation. Mouse lungs were obtained for histopathologic analysis and collagen assay (Wang et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunofluorescence analysis was performed as described previously (Wang et al, 2014). The following primary antibodies were employed: Rabbit anti-zonula occludens-1 (ZO-1); rabbit anti-occludin (all antibodies were purchased from Abcam, Cambridge, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Researches showed that the Wnt/β-catenin pathway is hyperactivated in lung from a subset of patients with IPF [17,18], and Wnt-3α promoted myofibroblast differentiation via Smad-dependent TGF-β signaling [19]. Our group have found that activated Wnt signaling induces myofibroblast differentiation of mesenchymal stem cells and inhibition of Wnt/β-catenin signaling promotes engraftment and epithelial differentiation of mesenchymal stem cells to repair lung injury [20][21][22]. Upon activation, β-catenin and Lef1/Tcf, which are downstream components of the Wnt signaling cascade, form a complex with Smad4, an essential mediator of signals initiated by TGF-β, then translocate to the nucleus to participate in transcription [23].…”
Section: Introductionmentioning
confidence: 94%